The Effect of Acute Phase Reactants on the Survival of COVID-19 Patients in Intensive Care - Orhan, Semiha; Tasdemir Mecit, Bilge Banu; Dizen Kazan, Elif; Kazan, Sinan; Şarlak Konya, Petek; Gulsoy, Kemal Yetiş (Progress in Nutrition, 2021)
Study Objectives: The aim of this study was to investigate the relationship between the biomarkers of serum CRP, PCT, D-dimer, ferritin, and lymphocytes, and the survival of COVID-19 patients admitted to the Intensive Care Unit (ICU). Methods: The effect of acute phase reactants on survival were retrospectively examined in 399 patients diagnosed with COVID-19 and followed up in the ICU of Afyonkarahisar Health Sciences University Medical Faculty Hospital between 20 March 2020 and 31 December 2020. Results: The 399 patients included in the study comprised 273 (68.4%) males and 126 (31.6%) females with a median age of 68 years (IQR: 15 years). Mortality developed in 225 (56.4%) patients in ICU and 174 (43.6%) were discharged. In the ROC analysis applied to CRP, PCT, D-dimer, ferritin levels, and lymphocyte count, the AUC values were determined in the range of 0.389-0.635. D-dimer was the parameter with the highest AUC value. In the survival analysis according to the cutoff values determined for CRP, PCT, D-dimer, and lymphocyte count, these four parameters were determined to have an effect on survival (p = 0.038, p = 0.001, p = 0.012, and p = 0.018, respectively). Ferritin levels were found to be similar between the groups of survivors and non-survivors (p = 0.492). Conclusion: High serum CRP, PCT, D-dimer levels, and low lymphocyte count were determined to be associated with poor outcomes in the 399 patients admitted to the ICU with a diagnosis of severe COVID-19 pneumonia.